Democratic dreams neglected in the land of the Pharaohs: US democracy assistance in Egypt - Rieffer-Flanagan, Barbara Ann J. (Human rights review, 2014)
This paper examines the Obama Administration’s approach to democracy promotion in Egypt. After a brief discussion of the motivation for promoting democracy, this essay compares the Obama Administration to its predecessor and analyzes the changes that were spurred by the Arab Awakening. Did the Obama Administration, during and after the 2011 Revolution, fully support democratic change in Egypt not only with rhetoric but also with the financial and programmatic support necessary to help a transitioning country? Did the Obama Administration offer a consistent message on the importance of democratic policies? Or did the administration allow other policy objectives to trump democratic efforts? This paper explores the language, policies, and funding employed by the Obama Administration in Egypt to see what the impact has been.